An annotated checklist of fur mites (Trombidiformes: Myobiidae) housed at the Acarological Collection of the Butantan Institute - Onrubia, Ana Carolina B.; Bassini-Silva, Ricardo; Pereira, Josivania S.; de Mello, Érica M.; Nitsche, Aline; Jacinavicius, Fernando de C. (Entomological Communications, 2022)
The fur mites (Trombidiformes: Myobiidae) are true parasites of mammals, especially bats, rodents, and marsupials. In the present study, we examined the fur mites housed at the Acarological Collection of the Butantan Institute (IBSP), Brazil, and providing an annotated checklist of the mites examined, including type species data, new host associations and new locality records.